SISTEM INFORMASI PEMANTAUAN PENJUALAN BARANG RONGSOKAN MENGGUNAKAN FRAMEWORK CI.4 PADA CV. SUMBER BAJA - Dicky Dicky; Kurniawan Kurniawan (Universitas Lancang Kuning, 2022)
Sumber Baja is a trading company engaged in used goods such as cans, iron, and junk which will be sent to the client. At the time of delivery the company is still making notes in the book to make a report on the delivery of goods. This system is intended for the design of sales monitoring applications that can assist in making reports on goods that have been sent to the client. Because it has several obstacles in using the system which is still recorded in the book. So the process of making reports takes a long time because of searching for data in the books, making file and document storage increasing which makes it difficult to find old data, and data loss often occurs which can make company leaders not know whether the goods sent were appropriate or not when sent. . research aims to create a sales monitoring information system on CV. Sumber Baja Palembang, so that it can help admins in making reports on sales of goods and making it easier to search for new or old data and avoid data loss. The system design technique used is the agile method and the implementation of this research uses the PHP programming language and the MYSQL database. The results of the study are expected to help admins store data on goods that have been sent and help make reports to find out the difference between goods.